Building the Education and Training Pillar of the University of Tennessee’s Institute for Nuclear Security - Howard Lewis Hall (International Journal of Nuclear Security, 2016)
The University of Tennessee (UT) developed its first formal and coordinated efforts in nuclear security education in 2008-2009 with its graduate certificate program in nuclear security in the Department of Nuclear Engineering. Building on this work, in 2011 UT established the UT Institute for Nuclear Security (INS) as a collaborative center at the university to expand its curricular impact as well as foster research and partnerships with nearby major governmental facilities engaged in nuclear security work. Oak Ridge National Laboratory (ORNL), the Y-12 National Security Complex (Y-12), and Oak Ridge Associated Universities (ORAU) have joined with UT as charter members of the INS. The INS has successfully fostered the development of a near-comprehensive nuclear security curriculum within multiple academic units. In addition to traditional academic offering, the INS is developing a comprehensive strategy for professional development short-course series that facilitates post-graduate entry into the nuclear security field and continuing education.
Keywords: Nuclear security; education; training; safeguards